2000
DOI: 10.1002/(sici)1096-9861(20000529)421:2<161::aid-cne3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

GABA neurons provide a rich input to microvessels but not nitric oxide neurons in the rat cerebral cortex: A means for direct regulation of local cerebral blood flow

Abstract: Basal forebrain neurons project to microvessels and the somata of nitric oxide (NO) synthase‐containing neurons in the cerebral cortex, and their stimulation results in increases in cortical perfusion. γ‐Aminobutyric acid (GABA) is the second major neurotransmitter synthesized by these neurons and it has also been reported to modify cerebromicrovascular tone. We thus investigated by light and electron microscopy the association of GABA neurons (labeled for glutamic acid decarboxylase [GAD]) with cortical micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 55 publications
0
69
0
Order By: Relevance
“…This increase in CBF is followed by a persistent decrease in blood flow (Lambert and Michalicek, 1994; Ayata et al, 2004) and oxygen levels (Piilgaard and Lauritzen, 2009) leading to a period of tissue hypoxia (Lukyanova and Bures, 1967; Lacombe et al, 1992; Otori et al, 2003; Takano et al, 2007). Therefore, in order to restore metabolic balance, cortical neurons including interneurons and astroglia are thought to release of a variety of neurotransmitters including NO, carbon monoxide, adenosine, hydrogen ions, potassium ions, and lipoxygenase products known to alter cerebral vascular tone (Cauli et al, 2004; Vaucher et al, 2000; Zonta et al, 2003; Filosa et al, 2006; Koehler et al, 2006; Busija et al, 2008). Independent of vascular tone, these signaling molecules also directly affect endothelial cell signaling pathways (De Caterina et al, 1995; Jozkowicz et al, 2003; Erlinge and Burnstock, 2008; Dalvi et al, 2015; Mark et al, 2001).…”
Section: 1 Cortical Spreading Depressionmentioning
confidence: 99%
“…This increase in CBF is followed by a persistent decrease in blood flow (Lambert and Michalicek, 1994; Ayata et al, 2004) and oxygen levels (Piilgaard and Lauritzen, 2009) leading to a period of tissue hypoxia (Lukyanova and Bures, 1967; Lacombe et al, 1992; Otori et al, 2003; Takano et al, 2007). Therefore, in order to restore metabolic balance, cortical neurons including interneurons and astroglia are thought to release of a variety of neurotransmitters including NO, carbon monoxide, adenosine, hydrogen ions, potassium ions, and lipoxygenase products known to alter cerebral vascular tone (Cauli et al, 2004; Vaucher et al, 2000; Zonta et al, 2003; Filosa et al, 2006; Koehler et al, 2006; Busija et al, 2008). Independent of vascular tone, these signaling molecules also directly affect endothelial cell signaling pathways (De Caterina et al, 1995; Jozkowicz et al, 2003; Erlinge and Burnstock, 2008; Dalvi et al, 2015; Mark et al, 2001).…”
Section: 1 Cortical Spreading Depressionmentioning
confidence: 99%
“…Such changes imply that the cerebral microcirculation must be highly responsive to the metabolic requirements of CNS tissue and suggests a need for direct innervation of the brain microvasculature. Indeed, there is considerable evidence for direct innervation of both brain microvessel endothelial cells and associated astrocyte processes via distinct connections with noradrenergic (66, 67), serotonergic (68), cholinergic (69, 70) and GABAergic (71) neurons. For example, studies have shown that loss of direct noradrenergic input from the locus coeruleus results in increased BBB susceptibility to effects of acute hypertension, resulting in significantly increased permeability to 125 -I labeled albumin (57).…”
Section: Components Of the Nvumentioning
confidence: 99%
“…Noradrenergic (183;184), serotonergic (185), cholinergic (186;187), and GABAergic (188) neurons have been shown to make distinct connections with other cell types of the neurovascular unit. The need for direct innervation of brain microvasculature comes from the dynamic nature of neural activity and the metabolic requirements of nervous tissue, implying that the cerebral microcirculation must be highly responsive to the needs of CNS tissue.…”
Section: Components Of the Neurovascular Unitmentioning
confidence: 99%